2007
DOI: 10.1063/1.2804081
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ferromagnetism upon thermal annealing in pure ZnO

Abstract: We report here enhancement of ferromagnetism in pure ZnO upon thermal annealing with the ferromagnetic transition temperature Tc above room temperature. We observe a finite coercive field upto 300K and a finite thermoremanent magnetization upto 340K for the annealed sample. We propose that magnetic moments can form at anionic vacancy clusters. Ferromagnetism can occur due to either superexchange between vacancy clusters via isolated F + centers, or through a limited electron delocalization between vacancy clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
156
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(174 citation statements)
references
References 16 publications
10
156
3
1
Order By: Relevance
“…23 A high concentration of V o could also promote the probable formation of anionic vacancy clusters which can induce sizable magnetic moments. 6 Although our result does not exclude other types of defects like cation vacancies as the origin of long range ferromagnetic ordering, 24,25 these defects often have higher formation energy than V o and can form only in oxygen rich environments. 26 Our experiments were carried out in oxygen poor conditions where V o always contributes to the nonstoichiometry.…”
Section: -mentioning
confidence: 91%
See 1 more Smart Citation
“…23 A high concentration of V o could also promote the probable formation of anionic vacancy clusters which can induce sizable magnetic moments. 6 Although our result does not exclude other types of defects like cation vacancies as the origin of long range ferromagnetic ordering, 24,25 these defects often have higher formation energy than V o and can form only in oxygen rich environments. 26 Our experiments were carried out in oxygen poor conditions where V o always contributes to the nonstoichiometry.…”
Section: -mentioning
confidence: 91%
“…Adding to these existing literatures, there have been a few notable reports on RTFM in undoped ZnO. Banerjee et al 6 reported the enhancement of ferromagnetism in pure ZnO powder upon thermal annealing, which was linked to the formation of oxygen vacancy ͑V o ͒ clusters. Xu et al 7 also reported ferromagnetism in ZnO thin films and attributed it to the intrinsic defects.…”
mentioning
confidence: 99%
“…10 However, the defects responsible for the observed ferromagnetism in nondoped ZnO are still under debate. Zn defects, [3][4][5] O vacancies, 6,7 and Zn nanoclusters embedded in ZnO matrix, 8 have been considered to be the possible origin. Theoretically, O interstitial, Zn vacancy and O vacancy (V O ) clusters have been suggested to induce the ferromagnetism in ZnO.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…Room temperature ferromagnetism has been observed in the traditionally nonmagnetic semiconductor oxide nanoparticles and films, such as ZnO, CeO 2 , Al 2 O 3 , In 2 O 3 , HfO 2 , and SnO 2 , etc., and the defects have generally been considered to be the origin. [1][2][3][4][5][6][7][8] ZnO is a wide band gap semiconductor (E g ∼ 3.3 eV at 300 K) and has a large exciton binding energy (∼ 60 meV), which has wide applications in optoelectronics.…”
mentioning
confidence: 99%
“…1(b), this approach forms a strong contrast with doping transition metals by avoiding the occurrence of unintentional clustering. Indeed, experimental observations of ferromagnetism in ZnO thin films 23 and pure ZnO powders 24,25 have been attributed to the intrinsic defects. It was also proposed that defects like Zn and O vacancies, 23,[26][27][28][29][30][31] [35][36][37][38][39][40][41] suggesting that the underlying physics is universal.…”
Section: Introductionmentioning
confidence: 99%